Calibrating conservation: new tools for measuring success - Kapos, Valerie; Balmford, Andrew; Aveling, Rosalind; Bubb, Philip; Carey, Peter; Entwistle, Abigail; Hopkins, John; Mulliken, Teresa; Safford, Roger; Stattersfield, Alison; Walpole, Matt; Manica, Andrea (Conservation Letters, 2008)
Conservation practitioners, policy makers, and donors agree that there is an urgent need to identify which conservation approaches are most likely to succeed in order to use more effectively the limited resourc es available for conservation. While recently developed standards of g ood practice in conservation are helpful, a framework for evaluation i s needed that supports systematic analysis of conservation effectivene ss. A conceptual framework and scorecard developed by the Cambridge Co nservation Forum help to address common constraints to evaluating cons ervation success: unclear objectives, ineffective information manageme nt, the long time frames of conservation outcomes, scarcity of resourc es for evaluation, and lack of incentives for such evaluation. For sev en major categories of conservation activity, the CCF tools help clari fy conservation objectives and provide a standardized framework that i s a useful basis for managing information about project outcomes and e xisting conservation experience. By identifying key outcomes that can predict conservation success and can be assessed in relatively short t ime frames, they help to make more efficient use of scarce monitoring and evaluation resources. With wide application, the CCF framework and evaluation tool can provide a powerful platform for drawing on the ex perience of past and ongoing conservation projects to identify quantit atively factors that contribute to conservation success.
Keywords: Conservation effect; Conservation outcomes; Evaluation; Evidence-based conservation; Monitoring; conservation impact; framework; indicators; scorecard